Latin American thought: operating the colonial fracture - Molina Araya, Andrés (2021)
This work seeks to understand the process of THE conquest and colonization in relation to the development of capitalism. This through the study of different authors of Latin American thought, who have theorized the reality of the continent at different times. In this way, it is about explaining the historical evolution of these lands in its different manifestations: economic, political and cultural. First, one will study the original accumulation of capital as a result of colonialism and conquest, then ONE WILL SEE the cultural process that arises, to later go on to analyze the emergence of the Nation States, ending, finally, with a reflection on how philosophical thought has been in the Latin American continent and the Caribbean. Thus, the present reality can be seen as the result of a historical process.